The Economic Impact of Overspecifying Simple Connections - Carter, Charles J.; Geschwindner, Louis F. (Engineering Journal, 1993)
An accurate and complete design will result in an economical and safe connection. Yet it is entirely common for the engineer of record to withhold, either intentionally or unintentionally, the information necessary to the fabricator or detailer to perform a design which is both accurate and complete. Specifically, actual reactions are seldom shown on the contract drawings from which the connections must be designed. AISC states, "For economical connections, beam reactions should be shown on the contract drawings. If these reactions are not shown, connections must be selected to support one-half the total uniform load capacity...for the given beam, span, and grade of steel specified." No quantification is given, however, of the actual difference in economy between the two cases. In fact, this difference is somewhat elusive as it may vary greatly among specific examples. For the general case, however, it is possible to determine a reasonable estimate of the economic sacrifice incurred when a larger connection than required is used. The focus of this paper, then, is this economic sacrifice. For simplicity, a standard configuration of the double angle connection will be considered in which only n, the number of bolt rows (and consequently, the length of the angles), varies. Based on values of n from 2 to 10, the cost of these standard connections will be estimated. Ranges of n compatible with each beam size group will be identified and the percent increase in cost which results when a larger connection than required is used will then be determined over these ranges. Note that the practices which routinely result in uneconomical connection designs are not specifically addressed in this paper. For a discussion of these practices, the reader is referred to "Eliminating the Guesswork in Connection Design—Communication of Design Requirements Between Fabricator and Engineer is Crucial for a Safe and Economic Structure" by W.A. Thornton, in the June 1992 issue of Modern Steel Construction. Also not addressed is the effect of standardization on the detailing costs, ease of fabrication, and overall quality of the constructed product. While in general, standardization will reduce detailing costs, increase the ease of fabrication, and lead to improvements in quality because of decreased variability, these considerations are more project related than connection specific. Thus, it would not be feasible to consider their effect in this paper.